'Post goblins' and 'preditors': identities, experiences, and contributions of women in Australian screen postproduction and visual effects sectors 2020/2021. Issue 1 (2nd January 2022) - Erhart, Julia; Dooley, Kath
ABSTRACT: The first 20 years of the twenty-first century have seen a flourishing of research about women film and media creatives, their industrial positioning, and media output in industries around the globe, but overwhelmingly this research has focussed on the woman director. Women below-the-line workers, their workplace experiences, and their impression of their own creative contributions, particularly in areas of editing, sound design, and visual effects, have been glaringly absent. This paper aims to spotlight the under-examined working conditions and creative contributions of women working in Australian postproduction and visual effects (VFX) areas, what their experiences and perceptions tell us about the sector more broadly at a time of decreasing job security and increasing demand for screen content since the time of COVID-19, and their perceptions about their own creative contributions. These findings are based on our analysis of semi-structured interviews that we carried out with 11 women workers in a range of geographical locations, of varying ethnicities, sexualities, and ages, and at different career points. The insights generated by these interviews speak to the challenges faced by these workers and their perceptions of their work and fill a gap in the feminist production studies literature, about women, postproduction, and VFX.